2022
DOI: 10.3390/nano12152527
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Activation and Hydrogenation on Cu-ZnO/Al2O3 Nanorod Catalysts: An In Situ FTIR Study

Abstract: CuZnO/Al2O3 is the industrial catalyst used for methanol synthesis from syngas (CO + H2) and is also promising for the hydrogenation of CO2 to methanol. In this work, we synthesized Al2O3 nanorods (n-Al2O3) and impregnated them with the CuZnO component. The catalysts were evaluated for the hydrogenation of CO2 to methanol in a fixed-bed reactor. The support and the catalysts were characterized, including via in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The study of the CO2 adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It appeared that basic sites were more easily accessible in the disordered catalyst, resulting in better CO 2 conversion and higher STY of methanol for the catalyst prepared at 450 °C. While basic sites are mostly characteristic of ZnO, [25] the reduction of the number of weak basic sites with an increase in crystallinity was also shown for the MgAl‐oxide support (Figure S7d, Table S2) due to the consumption of MgO to form AlMg‐oxide with increasing the temperature of thermal treatment. The basic sites at higher desorption temperatures were not evaluated as they resulted from strongly chemisorbed CO 2 that is not desorbed during the reaction conditions.…”
Section: Resultsmentioning
confidence: 80%
“…It appeared that basic sites were more easily accessible in the disordered catalyst, resulting in better CO 2 conversion and higher STY of methanol for the catalyst prepared at 450 °C. While basic sites are mostly characteristic of ZnO, [25] the reduction of the number of weak basic sites with an increase in crystallinity was also shown for the MgAl‐oxide support (Figure S7d, Table S2) due to the consumption of MgO to form AlMg‐oxide with increasing the temperature of thermal treatment. The basic sites at higher desorption temperatures were not evaluated as they resulted from strongly chemisorbed CO 2 that is not desorbed during the reaction conditions.…”
Section: Resultsmentioning
confidence: 80%
“…Metal oxides (MO x ) have been reported to serve as an ideal electroactive platform for surface functionalization and catalyst immobilization. This is because these MO x materials feature tuneable electronic properties, transparency, and affinity toward various functional groups (e.g., −PO 3 H and −COOH) that could be readily utilized for surface anchoring. Zhao et al have demonstrated that simply adding pendant acid/base relays on a TiO 2 surface can steer the ORR pathways, thereby switching the mechanism from a sequential single-electron transfer process to a concerted 4e – /4H + reduction process …”
Section: Introductionmentioning
confidence: 99%
“…This is because these MOX materials feature tuneable electronic properties, transparency, and affinity toward various functional groups (e.g., -PO3H, -COOH) that could be readily utilized for surface anchoring. [37][38][39][40][41][42][43] Zhao et al have demonstrated that simply adding pendant acid/base relays on a TiO2 surface can steer the ORR pathways, thereby switching the mechanism from a sequential single-electron transfer process to a concerted 4e -/4H + reduction process. [44] Taking advantages of MOx surfaces as a support for assembling multiple components, we herein describe the immobilization of a novel copper (II) dipicolylamine (denotes as CuL) complex on mesoporous nickel oxide (meso-NiO) surfaces to form surface-bound electrocatalyst for oxygen reduction in water.…”
Section: Introductionmentioning
confidence: 99%